Letter to the Editor—Comment on Dantzig's Paper on Discrete Variable Extremum Problems - Bellman, Richard (Operations Research, 1957)
In his interesting paper on discrete-variable extremum problems, George Dantzig (Dantzig, G. 1957. Discrete-variable extremum problems. Opns Res. 5 266–277.) discusses the “knapsack” problem. He presents two approximate methods based upon linear programming techniques, and an exact solution based upon the functional equation method of dynamic programming (Bellman, R. 1957. Dynamic Programming. Princeton University Press.).